O site educativo learnenglish kids como recurso pedagógico nos processos de ensino aprendizagem de língua inglesa - Santos, Marina Belló dos (My University, 2019)
The present research has the aim of analyzing, based on Vygotsky’s theory, an educational website directed to the English Language teaching and if this resource can be considered a mediator of the learning and teaching processes. The theorical framework has its basis on the mediational, internalization, interaction, zone of proximal development and sociointeraction concepts from Vygotsky articulated with authors from the educational and English teaching and learning area. The research was applied in a regular school with students that stay in school during all day, from the fourth and fifth year. The corpus was elaborated from videos, student’s production and the teacher notes obtained using the LearnEnglish Kids website. Moraes and Galiazzi base the corpus treatment on textual discursive analysis, from where analysis categories emerged. The articulation of these categories, having the theorical framework, permitted identifying the contributions of this educational website to the English language teaching and learning processes. During the workshops, it was possible to notice moments of mediation, interaction, and sociointeraction among the research participants and the teacher/researcher. In these moments, knowledge mobilization and construction in relation to the English language were perceived. Other important moments were evidenced, like the performance in the zone of proximal development of the students. In this research, the educational website was identified as an instrument of mediation, but it also stands out the importance of the presence of a mediational teacher who can make interventions, using the website, in order to collaborate to the teaching and learning processes.
A presente pesquisa tem como objetivo analisar, a partir dos pensamentos de Vygtsky, um site educativo direcionado ao ensino da língua inglesa e se este recurso pode ser considerado um mediador dos processos de ensino aprendizagem dessa língua. O quadro teórico tem como base os conceitos de mediação, internalização, interação e zona de desenvolvimento proximal de Vygotsky, articulado com autores da área da educação e do ensino aprendizagem da língua estrangeira. A pesquisa foi aplicada numa escola regular do ensino básico com alunos participantes do turno integral de 4º e 5º ano do Ensino Fundamental. O corpus da pesquisa foi produzido a partir de vídeogravações, produções de educandos e anotações da pesquisadora obtidos a partir de oficinas aplicadas aos alunos, fazendo uso do site educativo LearnEnglish Kids. O tratamento do corpus se deu a partir da análise textual discursiva de Moraes e Galiazzi, de onde emergiram categorias de análise. A articulação dessas categorias emergentes, tomando o quadro teórico, permitiu identificar as contribuições do uso do site educativo para o ensino aprendizagem de língua inglesa. Durante as oficinas a partir do site educativo, percebeu-se que existiram momentos de mediação, interação e sociointeração entre os participantes da pesquisa e a professora/pesquisadora. Nesses momentos foram percebidos mobilização e construção do conhecimento em relação à língua inglesa. Foram evidenciados também, momentos de atuação na zona de desenvolvimento proximal do aluno. Nesse estudo, o site foi identificado como instrumento mediador dos processos, porém também ressalta a importância da presença de um professor mediador que faça intervenções a partir do uso do site educativo colaborando com processos de ensino aprendizagem.
Keywords: Sites da Web - Métodos de ensino; Língua inglesa (Ensino fundamental); Aprendizagem; Ambientes virtuais compartilhados; Mediação; Web sites - Teaching methods; English language (Elementary School); Learning; Shared virtual environments; Mediation